Ruido ambiental y su relación con percepción acústica en pobladores de la avenida Quiñones 2024 - Sotelo Lescano, Luis Olabo (2025)
The exposure of residents of Quiñones Avenue to envirenmental noise levels exceeding permitted limits can cause health problems and discomfort. The study aimed to establish a relationship between envirenmental noise and acoustic perception, in addition to comparing the levels of these variables with sociodemographic factors. The study was quantitative, with a non experimental, cross-sectional, correlational design. The population consisted of Quiñones Avenue residents. A probability sampling was used, with a sample of 384 residents. Surveys and observations were used. Instruments included a questionnaire and an observation form for the data provided by the sound level meter. SPSS v23 software was used to evaluate the data. The results showed that the environmental noise level on Quiñones Avenue was extremely high (87.5%), which could affect health, performance, and concentration, and very high (12.5%), where people reported difficulty concentrating, distraction, discomfort, and fatigue, but not in all cases. The acoustic perception of residents of Quiñones Avenue was moderate in 51.2%, low in 39.2%, and high in 9.6%. It was concluded that there is a relationship between environmental noise and acoustic perception (r=0.768; p=0.000<0.05; high correlation).